Global memories, inclusive classrooms. An analysis of the theoretic proposals for a “universalization” in school historiography (1991-2015) - Escribano Roca, Rodrigo (Clio. History and History Teaching, 2018)
The main purpose of this essay is to analyse the increasing demands of scholars and international organisations for a “universalisation” with regard to both contents in history textbooks and teaching history syllabus. To that end, we analyse comparatively the theories and official texts that have contended the ideas of “integration” and “inclusive education”. Likewise, we put them in dialogue with a group of historiography essays that have claimed for a “globalisation” in school history textbook´s contents. We discuss if “universalisation” is an ideal path to instill civic and cross-cultural values in students.
Keywords: school historiography; integration; nationalism; universalisation; cross-culturality; textbooks; globalization